ANALYTICAL HIERARCHY PROCESS (AHP) APPROACH IN DETERMINING PRODUCT-BASED MARKETING STRATEGIES FOR MSMEs - Nurfadila, Agustin Rani; Varian, Ahmad; Negara, Palmadi Putri Surya; Dwicahyo, Agung (Universitas Veteran Bangun Nusantara, 2025)
One of the priorities of development in the Government Work Plan is the development of Micro, Small, and Medium Enterprises (MSMEs). This research aims to formulate a marketing strategy for the MSME engaged in processing rengginang in Mojopitu Village, Slahung District, Ponorogo Regency, in order to enhance competitiveness and expand market reach. MSMEs play a strategic role in the regional economy, especially in creating jobs and driving economic growth. One of the MSMEs in Mojopitu Village produces rengginang, which still faces various challenges in marketing. The method used is the Analytical Hierarchy Process (AHP) supported by Microsoft Excel to analyze the best marketing strategies based on interviews with experts and MSME practitioners. Primary data was obtained through direct interviews, while secondary data was collected from literature reviews and related reports. The research results indicate that the main factor with priority is the product with a maximum weight of 0.666, showing that product innovation and quality play a key role in business success. Regarding the objectives, it is argued that increasing sales with a weight of 0.818 is the top priority, and that marketing strategies should focus on increasing sales volume. The most effective alternative strategy is digital marketing with a maximum weight of 0.620. This suggests that the use of technology and digital platforms is a key step in enhancing competitiveness and achieving marketing goals. Therefore, it is recommended to prioritize product innovation, increase sales, and trigger digital marketing strategies to enhance competitiveness and sustainable growth.